ANALISIS LAY OUT PROSES TIWUL INSTAN “SRIKANDI” PADA PT SUKSES MAKMUR SENTOSA DI DESA MUNGGI KECAMATAN SEMANU KABUPATEN GUNUNG KIDUL - Lusi Yanuke Astarini; Juarini Juarini (Jurnal Dinamika Sosial Ekonomi, 2007)
Analysis Layout Process Srikandi Tiwul Instant In PT. Sinar Sukses Sentosa in Village Semanu Subdistrict Gunung Kidul Regency aim to know about layout process in PT. Sinar Sukses Sentosa and give the alternative of effisient layout process Srikandi Tiwul  Instant. The research method is case study.this research is used primary and secondary data from PT. Sinar Sukses Sentosa in Munggi village Semanu Subdistrict Gunung Kidul Regency. The analysis model used is load Distance. Research result indicate those layout process on this time has not been effisient. Alternative layout process more effisient than layout process on this time.Key words : Layout Process, Tiwul Instant